Influence Of Personality Traits, Job Satisfaction And Employee Farming On Job Performance: A Study Among Engineering Firms In Malaysia - Leong, Tony Weng Beng (2020)
This research is targeted at individuals performing engineering roles who work in Electrical and Electronics based companies in Malaysia. It focusses on Personality Traits (for talent acquisition), Job Satisfaction (for talent retention) and ‘Employee Farming’ (for talent growth). The study strives to achieve 3 objectives. Firstly, it investigates how Personality traits affect Job Performance. Secondly, it tests if Job Satisfaction is a mediator between Personality traits and Job Performance. Thirdly, it introduces the concept of ‘Employee Farming’ and tests if it is a moderator to the Personality traits - Job Performance relationship.